POLA ASUH ORANG TUA, DUKUNGAN SOSIAL DENGAN PERILAKU BULLYING PADA SISWA PEREMPUAN - Purukan, Gebby; Wetik, Syenshie; Laka, Angela (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2022)
Introduction: The problem of bullying generally occurs at the age of teenagers, for example, physical bullying, verbal and cyberbullying. Parenting patterns and social support can influence bullying behavior. Good parenting or not can make teenagers behave in bullying. High and low levels of social support can also make teenagers do bullying behavior. The perceived impacts are anxiety, stress, depression, withdrawal from the environment, mental health disorders, and suicide. If this case is not resolved, it will threaten the future of teenagers. Objective: The purpose of this study was to analyze the relationship between parenting, social support, and bullying behavior in female students. Method: The method is quantitative, uses a descriptive correlational research design with a cross-sectional study approach. The sampling technique used was the total sampling technique, with a sample of 90 female students. Result: The results of this study indicate that the most obtained is high bullying behavior, the parenting pattern shows that most parenting patterns are not good, for the most with a low level of social support. From these results, it was found that there was a significant relationship between parenting and bullying behavior in female. The relationship between social support and bullying behavior shows significance. Conclusions: There is a significant relationship between parenting style and bullying behavior, and there is a significant relationship between social support and bullying behavior in SMP N 3 Tombatu students.